5 - Parents’ Engagement in Adult Literacy and its Impact on their Children’s Schooling - Amenyah, Efua Irene (Africa Development, 2021)
This study examined the positive impact of adults’ engagement in literacy classes and its relation to the retention and performance of their children’s schooling. It was hypothesized that adults who are pursuing personal goals by engaging and attending literacy classes when perceiving the instrumentality value of the learning activities have their children attend and succeed at their schooling. A mixed research methodology combining qualitative and quantitative approaches was used to collect and analyse data. Respondents included 132 adult learners and 20 volunteer teachers from ten different adult literacy classes across Togo. Results have shown that adults who engaged in learning and performed and persevered while attending literacy classes, show positive behaviours to their children and consequently were able to be involved in their children’s schooling by encouraging them to learn for better achievement and performance in school.